2022
DOI: 10.3390/min12121561
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Far Infrared Spectroscopy for NaCl and KCl Minerals Characterization—A Case Study of Halides from Kłodawa in Poland

Abstract: The paper presents research on chloride minerals of natural origin from Kłodawa (Poland), i.e., colorless, blue and purple halite as well as colorless sylvite. Selected samples of minerals were studied by chemical analysis (ICP-OES, ICP-MS, titration methods) and crystallographic measurements. Then, for the tested halides, research was carried out using far-infrared spectroscopy. Spectroscopic studies confirmed the simple way of distinguishing NaCl and KCl minerals using far-infrared spectroscopy, known in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…No imaginary frequencies were determined. In our previous study on LiCl, NaCl, KCl, LiBr and LiF, calculations using a 125-atom model for very similar chemical compounds to those mentioned, gave reliable results [43,44]. The theoretical IR spectrum of the structure of sodium fluoride was derived by representing each band as a Lorentzian-shaped curve.…”
Section: Dft Calculationsmentioning
confidence: 95%
See 1 more Smart Citation
“…No imaginary frequencies were determined. In our previous study on LiCl, NaCl, KCl, LiBr and LiF, calculations using a 125-atom model for very similar chemical compounds to those mentioned, gave reliable results [43,44]. The theoretical IR spectrum of the structure of sodium fluoride was derived by representing each band as a Lorentzian-shaped curve.…”
Section: Dft Calculationsmentioning
confidence: 95%
“…We observed the same relationship for a series of chlorides. The most intense bands for LiCl, NaCl and KCl, were observed at 200, 175 and 145 cm −1 , respectively [43,44].…”
Section: Far Infrared Spectrum Of Villiaumitementioning
confidence: 97%
“…The input geometries of salt crystal models (LiF, LiCl and LiBr) were taken for calculation from crystallographic data [50][51][52]. Our previous study showed that calculations for a 125-atom model for NaCl and KCl give reasonable results [41]. This 125-atom structure provides that each of the 27 atoms of the conventional unit cell of the studied lithium halides has six-fold coordination.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…This 125-atom structure provides that each of the 27 atoms of the conventional unit cell of the studied lithium halides has six-fold coordination. Moreover, according to our previous study for NaCl and KCl, freezing of all bond angles to 90 • in the structure during the geometry optimization process leads to a good simulation of the lattice parameters of the crystals and their infrared spectra [41]. Thus in this work, the geometries of the 125-atom model structures of LiF, LiCl and LiBr were fully optimized with the restriction for all angles 90 • .…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation